2013
DOI: 10.1007/s12594-013-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation and its Mechanisms: A Review of Exhumation Studies in the Himalaya

Abstract: Exhumation has been recognised as a key factor in understanding the dynamics of a mountain belt. Normal faulting, erosion and ductile thinning are the three basic mechanisms to exhume the deeper high grade metamorphic rocks to the surface. Convergent orogenic belts are characterised by over-thickening of the crust due to thrusting and folding. The interplay of uplift due to over-thickening of crust and climatic-erosion is the most plausible mechanism of exhumation as suggested by the numerical models and analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 153 publications
0
13
0
Order By: Relevance
“…Apatite fission track exhumation rates in western Bhutan (1.4 mm yr −1 since 2.5 Ma) are higher than those in eastern Bhutan (0.7 mm yr −1 since 5.1 Ma), and may reflect a difference resulting from the uplift of the Shillong Plateau in northern India ( Fig. 1A; Grujic et al, 2006;Biswas et al, 2007;Adlakha et al, 2013a;Coutand et al, 2014). The Shillong Plateau creates an orographic rain shadow along the front ranges in eastern Bhutan (Fig.…”
Section: Study Locationmentioning
confidence: 97%
See 1 more Smart Citation
“…Apatite fission track exhumation rates in western Bhutan (1.4 mm yr −1 since 2.5 Ma) are higher than those in eastern Bhutan (0.7 mm yr −1 since 5.1 Ma), and may reflect a difference resulting from the uplift of the Shillong Plateau in northern India ( Fig. 1A; Grujic et al, 2006;Biswas et al, 2007;Adlakha et al, 2013a;Coutand et al, 2014). The Shillong Plateau creates an orographic rain shadow along the front ranges in eastern Bhutan (Fig.…”
Section: Study Locationmentioning
confidence: 97%
“…1B inset), which may (Grujic et al, 2006;Biswas et al, 2007) or may not (Adlakha et al, 2013b;Coutand et al, 2014) have caused decreased erosion rates and thus decreased erosion-driven exhumation rates. In contrast, greater precipitation along the western Bhutanese front ranges may facilitate higher exhumation rates and oversteepened slopes in the Puna Tsang Chhu region (Duncan et al, 2003;Grujic et al, 2006;Adlakha et al, 2013a). The far northern reaches of the Puna Tsang Chhu basin are glaciated and fed by the summer monsoonal precipitation with evidence for numerous glacial advanceretreat cycles since the Pleistocene (Iwata et al, 2002;Meyer et al, 2009).…”
Section: Study Locationmentioning
confidence: 99%
“…Two most recent reviews by Adlakha et al (2013a) and Thiede and Ehlers (2013) have observed large spatial and temporal variations in the Himalayan exhumation. Adlakha et al (2013a) have correlated the surface structures with the thermochronological ages and suggested that local tectonics of the area is the main factor controlling the exhumation.…”
Section: Figure 1 (A)topographic Map Of the Himalaya (Topography Basmentioning
confidence: 99%
“…Two most recent reviews by Adlakha et al (2013a) and Thiede and Ehlers (2013) have observed large spatial and temporal variations in the Himalayan exhumation. Adlakha et al (2013a) have correlated the surface structures with the thermochronological ages and suggested that local tectonics of the area is the main factor controlling the exhumation. Thiede and Ehlers (2013) remained focus over the temporal variations in exhumations and differentiated the patterns of denudations along the frontal ranges and northern higher elevation ranges over different span of time.…”
Section: Figure 1 (A)topographic Map Of the Himalaya (Topography Basmentioning
confidence: 99%
“…Considering the fact that the eastern Himalaya has experienced >5-10 km of crustal denudation since ca. 15 Ma (Grujic et al, 2006;Yin et al, 2010;Adlakha et al, 2013;McQuarrie and Ehlers, 2015;Adams et al, 2015), the morphologic and related sedimentological records of the inferred river (i.e., a linked longitudinal-transverse river flowing over the Himalayan crest) must have been erased. To resolve this issue we investigated the Quaternary geomorphologic and sedimentologic evolution of a Quaternary valley-fill sequence across a segment of the Yarlung-Subansiri divide in the eastern Himalaya (Fig.…”
Section: Namche Barwamentioning
confidence: 99%